Low‐temperature plasma‐jet‐activated medium inhibited tumorigenesis of lung adenocarcinoma in a 3D in vitro culture model. Issue 11 (6th September 2021) - Li, Ying; Lv, Yang; Tang, Mengxiong; Choi, Eun H.; Wang, Junjie; Lv, Guoqing; Zhu, Yu; Wang, Shubin; Liu, Yajie
Abstract: Many studies have shown, using two‐dimensional culture, that low‐temperature plasma‐jet‐activated medium (PAM) inhibits the growth of various tumor cells, whereas its effects and mechanisms in the three‐dimensional (3D) culture system remain unclear. In this study, a 3D cell culture model was used to study the inhibition of tumorigenesis of PAM in vitro. Our results showed that PAM significantly suppressed tumor spheroid formation and downregulated stemness‐related genes of A549 cells "before, " "during, " and "after" sphere formation. Additionally, we found that the specific signature of reactive oxygen species‐induced autophagy was involved in the antiproliferation effect of PAM on A549 spheroids. Our study complemented and extended the application of PAM for its anticancer effects in lung adenocarcinoma cancer. Abstract : Extensive research has shown that low‐temperature plasma‐activated medium (PAM) has potential anticancer capabilities. However, its use is still limited in clinical practice. In this study, we applied a three‐dimensional (3D) in vitro cell culture system. Our data confirmed that PAM treatment significantly suppressed the spheroid formation and stemness marker expressions of lung cancer stem‐like cells "before, " "during, " and "after" the formation of spheres. Besides, we found that the specific signature of reactive oxygen species‐induced autophagy was involved in the antiproliferation effect of PAM on 3D A549 spheroids. Our results indicated the potential antiproliferation role of PAM in the different stages of lung cancer treatment.